The impact of the health crisis on sports organizations - FILALI ALLACH Mariam ,; BENNANI Hayat ,; BELKADI Issam , (African Scientific Journal, 2022)
The effects of COVID-19 continue to felt in the health field, educational, financial and business institutions around the world, and the sports ecosystem is no different. Containment has caused sports sessions to cancel. Clubs and venues have had to close their doors. Owners, broadcasters and sponsors are trying to manage the impacts and implications of event cancellations and modifications. The situation has raised many questions. How do you simultaneously manage the costs, minimize the facts, and plan for a future that, in the short and long term, may no longer look like the past? Can new technology help businesses be more resilient? Have grants and facilities helped businesses cope with the crisis? As the pandemic looks set to last for some time, will the entire sports ecosystem have to find new ways to deal with threats to financial and business continuity due to disrupted cash flow, redundancy and recruitment issues?